SAT0042 Treatment by anti-IL-6 receptor acts on CD4+ FOXP3+ regulatory t cells in a model of rheumatoid arthritis. (23rd January 2014) - Thiolat, A.; Biton, J.; Semerano, L.; Lemeiter, D.; Boissier, M.-C.; Bessis, N.
Abstract : Background: Studies have demonstrated the clinical efficacy of tocilizumab, a humanized anti-IL-6 receptor (R) antibody (Ab), in patients with rheumatoid arthritis (RA). The rational for blocking IL-6 in this disease mainly lays on the pro-inflammatory role of this cytokine in the disease. Moreover, IL-6 acts as a "pivot", determining whether an immune response is dominated by regulatory CD4 + Foxp3 + T cells or Th17 effector T cells. However, only few works have studied the consequences of anti-IL-6R treatment on Tregs cells and only focuses on their frequency. Objectives: In this study, we hypothesized that IL-6 inhibition led to Tregs modifications in RA models given that (i) anti-IL6R is therapeutic in RA and its models by inhibiting Th17 cells, and (ii) IL-6 plays a determining role in inducing Th17 when present, or Tregs when it is absent. Our objective was thus to elucidate anti-IL-6R mode of action in RA models by studying the consequences of this treatment on Tregs phenotype and biological activity. Methods: Mice with collagen-induced arthritis were treated by MR16-1 (a rat anti-mouse IL-6 receptor monoclonal Ab provided by Chugai Pharmaceutical Co. LTD, Japan) and the evolution of Tregs (defined as CD4 + FoxP3 + ) during arthritis course was assessed at key time points (day 9-17-28 and 43 after CIA induction) by studying their number, frequency and phenotype (expression of GITR, ICOS, Helios, CD62L, CTLA-4 and CD39) in lymph nodes (LN) and spleen by flow cytometry. Finally, the immunosuppressive activity of the Treg cells on CFSE-labeled CD4+ CD25- T effector (Teff) cells proliferation was also studied. Numerical analysis of Th17 and Th1 cells was also performed at the same times by flow cytometry. Results: Clinical evaluation of arthritides in mice treated with anti-mouse IL-6R mAb showed, as expected, a less severe disease as compared to control Ig treated mice. A decreased Teff/Tregs ratio overtime were observed in the LN of MR16-1 treated mice. Tregs phenotype was modified in treated mice mostly at day 17, with a decreased frequency of Tregs expressing CD62L or Helios (spleen) but an enhanced intensity of CD39 expression on Tregs (spleen and LN) and increased frequency of CD39+ Tregs (LN). No modification in ICOS, GITR and CTLA-4 were observed on Tregs at any time in any compartments. Lastly, the immunosuppressive activity of the Treg cells on Teff cells proliferation was not modified, suggesting that Tregs immunosuppression activity was probably due to another mechanism. Conclusions: Tregs are modified by anti-IL-6R treatment in CIA, that could result in an enhanced peripheral generation of Tregs (Helios down regulation), an increased Tregs activation (CD39+ upregulation) and a better capacity to leave the secondary lymphoid organs and to migrate within the inflammatory joint (decreased CD62L down regulation). All together, thisstudy shows that inhibition of IL-6 in CIA also acts by modifying Tregs state. Disclosure of Interest: None Declared